IDENTIFICATION OF MICROFILARIAE USING CONVENTIONAL POLYMERASE CHAIN REACTION AND QPCR-HRM - Ihsan, Bagus Muhammad; Lakshmi Puspita, Widyana; Triana, Linda; Wahdaniah; Khayan; Dani Sucipto, Cecep (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: The presence of filarial worms in the lymph nodes can result in acute symptoms, such as inflammation of the lymph nodes and ducts, particularly in the groin region. As part of the life cycle of filariasis, symptomatic or asymptomatic patients with microfilariae in their blood can transmit the disease via mosquito bites. The inspection of microfilariae that is currently being developed uses Polymerase Chain Reaction (PCR) to carry out a unique DNA search technique. Purpose: Identify the type of microfilaria present in filariasis patients using Quantitative PCR High- Resolution Melting (qPCR-HRM) and conventional PCR techniques. Method: This study involved the examination of 19 samples using the qPCR-HRM method. Subsequently, the results that were considered positive for microfilaria underwent further testing using conventional PCR. Result: The results of the examination using these two methods revealed the presence of Brugia malayi and Wuchereria bancrofti microfilariae with peak melting temperatures ranging from 78.2 – 78.7 °C and 80.8 – 81.2 °C, and fragment sizes of 199 bp and 227 bp, respectively. Conclusion: Based on the results of the identification from these two methods, it is evident that microfilariae of Brugia malayi and Wuchereria bancrofti can be detected using both conventional and qPCR-HRM methods.